Modeling world Englishes assessing the interplay of emancipation and globalization of ESL varieties - Deshors, Sandra C.; Kautzsch, Alexander, 1969-2018 (Varieties of English around the world. General series ;, 2018)
At a time when globalization and the advent of the internet have accelerated the spread and diversification of English varieties worldwide, this book provides a constructive assessment of the theoretical models that best account for the development and use of Englishes in the early 21st century. In this endeavor, the present book brings together cutting-edge contributions by leading scholars who explore the notion of linguistic globalization based on a wide range of ESLs, EFLs and ELF, synchronic and diachronic data, different methodological approaches (corpus-based, sociolinguistic, ethnographic), and a variety of data resources (social media, multiplayer online games, journalistic data, GloWbE, Corpus of Historical Singapore English, thematic blogs). Collectively, these studies serve as a springboard for future research on the globalization of Englishes and they contribute to a timely and necessary scholarly conversation on what constitutes adequate theoretical models of World Englishes in the 21st century.